Metal Powder Applies to Vitrified Bond Diamond Abrasive - Shan, D.D.; Li, Z.H.; Yu, Y.Y.; Ye, H.; Zhu, Y.M. (Asian Journal of Chemistry, 2011)
Vitrified bond diamond abrasive was prepared by sintering diamond grains (3.5 μm) with low temperature vitrified bonds in air. In this work, Cu and Co were chosen as the additives to yield more gratifying abrasive. The fluidity and the wetting angle were investigated to characterize the flowing ability and wettability, mechanical property of samples were analyzed by means of single particle compressive strength and the interfacial bonding states between diamond grains and vitrified bonds were observed by scanning electron microscope (SEM). The results indicated that the properties of vitrified bond were meliorated by adding appropriate amount metal powder by which the mechanical property of diamond abrasive was promoted.